(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This scientific article presents a scientific analysis of the prevalence, etiology, pathogenesis, clinical symptoms, diagnostic methods, and modern treatment of kidney stones (nephrolithiasis). According to research, early detection of kidney stones reduces the rate of complications by 60-70%. The article also compares and analyzes the effectiveness of dietary, drug, and minimally invasive surgical approaches.